PEMBERDAYAAN KELOMPOK TANI MUDA MELALUI PELATIHAN PEMBUATAN KOMPOS RAMAH LINGKUNGAN DI DESA PETUNGSEWU - Priska Dwi Laurensia; Muhammad Mashia Abiyyu Arhab; Muhammad Husnul Wafa; Muhammad Iqbal Ramadhan; Muhammad Ivan Ardiansyah; Isyana Dwi Aryaningsih; Fara Widya Ramadhani; Hillmy Fu'addzan Nugroho; Umi Fatimah; Andri Prasetyo; Ninda Khairun Nisa (Jurnal Riset Multidisiplin Edukasi, 2026)
The issue of household organic waste management remains an environmental problem that has not been optimally addressed in rural areas. Organic waste that is not properly managed has the potential to cause environmental pollution, while on the other hand it has the potential to be used as compost that is beneficial for agriculture. This community service activity aims to increase the knowledge and skills of the Petungsewu Village Young Farmers Group in managing household organic waste into environmentally friendly compost and to encourage the implementation of sustainable waste management. The implementation method uses a participatory approach through the stages of problem identification, socialization, training, interactive discussions, hands-on composting practices, and activity evaluation. The results showed an increase in participants' understanding of the types of organic waste, the basic concepts of composting, the stages of composting, and practical composting skills. The activity also raised environmental awareness and encouraged behavioral changes in the community in waste management. The program had a positive impact in supporting environmentally friendly and sustainable agriculture. It is recommended that the activity be continued through assistance and replication of the program with the support of the local village government.